Affective abandonment in childhood and psychological damage: An integrative literature review (Research, Society and Development, 2022)
The subject of the present study addresses a subject that is part of the reality of many children who are victims of affective abandonment, which has consequences in their psychological formation. The family is the child's first constitution and has a strong influence on all stages of its development. Following this assumption, the research aims to analyze the psychological consequences caused by affective abandonment in childhood, studying its main consequences. The article performs an Integrative Literature Review as a methodology, which consists of conducting research that enables the synthesis, identification and structuring of knowledge for the elaboration of new interventions on the subject. It will use the BVS Platform, Library of Medicine (MEDLINE), Scientific Electronic Library Online (Scielo) as a database.